"What's happening to me?" : the answers to some of the world's most embarrassing questions - Mayle, Peter; Robins, Arthur (New York, NY : L. Stuart/Kensington, 1975)
Discusses the mental and physical changes that take place during puberty.
Keywords: Puberty -- Juvenile literature; Puberty; Adolescence